Autophagy, Cellular Aging and Age-related Human Diseases - Cheon, So Yeong (Exp Neurobiol, 2019)
Macroautophagy/autophagy is a conserved degradation system that engulfs intracytoplasmic contents, including aggregated proteins and organelles, which is crucial for cellular homeostasis. During aging, cellular factors suggested as the cause of aging have been reported to be associated with progressively compromised autophagy. Dysfunctional autophagy may contribute to age-related diseases, such as neurodegenerative disease, cancer, and metabolic syndrome, in the elderly. Therefore, restoration of impaired autophagy to normal may help to prevent age-related disease and extend lifespan and longevity. Therefore, this review aims to provide an overview of the mechanisms of autophagy underlying cellular aging and the consequent disease. Understanding the mechanisms of autophagy may provide potential information to aid therapeutic interventions in age-related diseases.